2019
DOI: 10.1111/jocd.12969
|View full text |Cite
|
Sign up to set email alerts
|

Innovative techniques for thread lifting of face and neck

Abstract: Background To investigate the efficacy and outcomes associated with eyebrow, midface, mandibular, and neck lifting using the innovative techniques. Materials and Methods In this prospective review chart study, a total of 151 patients, were included in the study from January 2016 to May 2017. All participants underwent thread lifting using our innovative thread‐lift technique for head and neck. The patients were followed up first week, first, third, and sixth month after lifting surgery. Outcomes were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
3
19
1
Order By: Relevance
“…In the present study, the relationship between the complications and the site of lifting was also shown to be significant only for ecchymosis, and there was no statistically significant relationship between other types of complications. In a study previously developed by Rezaee et al (2019), it was found that there was no significant relationship between postoperative complications and site of lifting, which was not in line with the results of this study 4 …”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…In the present study, the relationship between the complications and the site of lifting was also shown to be significant only for ecchymosis, and there was no statistically significant relationship between other types of complications. In a study previously developed by Rezaee et al (2019), it was found that there was no significant relationship between postoperative complications and site of lifting, which was not in line with the results of this study 4 …”
Section: Discussioncontrasting
confidence: 85%
“…Patients' satisfaction increased from 77.5% in the first week after surgery to 89.4% in the sixth month. For surgeon number one, rates of satisfaction in the end of first week and six month, were 96% (unchanged) 4 . As the same as this study (present study), the highest rate of operative satisfaction was reported in mandibular area and only for surgeon number 2 and in the first week there was a statistically significant relationship between satisfaction with the region of lifting and at other times no statistically significant association was found.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations